(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The rise of the e-commerce industry in Indonesia started 10 years ago and Indonesia is predicted as the market leader in Southeast Asia by 2025. The growth of this industry is driven by an increasing number of middle-class millennial consumers who are technology savvy and have higher purchasing power. Despite the importance of this consumer segment, there are limited studies about the intention of middle-class millennial consumers to purchase through e-commerce, particularly in developing countries, such as Indonesia. This study intends to examine the factors leading to consumer intention to shop online by including perceived security and perceived privacy to extend the theory of Technology Acceptance Model (TAM). Data were collected from 187 respondents and analyzed using PLS-SEM. The findings showed that perceived usefulness, perceived ease of use, perceived security, and perceived privacy influences consumers’ intention to shop in e-commerce, which was mediated by their attitude toward e-commerce. Among these influencing factors, perceived usefulness had a greater role in shaping consumer attitudes toward e-commerce than perceived ease of use, perceived security, and perceived privacy..